2020
DOI: 10.1364/oe.395227
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and improving the output power of terahertz master-oscillator power-amplifier quantum cascade lasers

Abstract: A model based on carrier rate equations is proposed to evaluate the gain saturation and predict the dependence of the output power of a terahertz master-oscillator power-amplifier quantum cascade laser (THz-MOPA-QCL) on the material and structure parameters. The model reveals the design rules of the preamplifier and the power extractor to maximize the output power and the wall-plug efficiency. The correction of the model is verified by its agreement with the experiment results. The optimized MOPA devices exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Notably, in the terahertz (THz) frequency range, the merging between the photonic and electronic concepts aroused a variety of novel cavity designs for high power single-mode terahertz quantum cascade lasers (THz-QCLs). For example, the third-order distributed feedback THz-QCLs were proven to be promising for low-divergence beam emission and high power efficiency . Biasco et al demonstrated continuous-wave highly efficient low-divergence terahertz wire lasers .…”
mentioning
confidence: 99%
“…Notably, in the terahertz (THz) frequency range, the merging between the photonic and electronic concepts aroused a variety of novel cavity designs for high power single-mode terahertz quantum cascade lasers (THz-QCLs). For example, the third-order distributed feedback THz-QCLs were proven to be promising for low-divergence beam emission and high power efficiency . Biasco et al demonstrated continuous-wave highly efficient low-divergence terahertz wire lasers .…”
mentioning
confidence: 99%